Rapporto tra diritto canonico e diritto consuetudinario in materia di dote - Nke Ongono, Jean Olivier (Dopo di noi, 2025)
In the classical era of canon law, dowry was a prerequisite for a valid marriage. This is no longer the case. The present paper, starting from a historical approach, shows how relevant it could be for canon law not to ignore the dowry, at least for an effective pastoral approach to marriage. Questions of property law between spouses and heirs would fall within the exclusive competence of the civil legislator.